Intelligent Wearable Device for Coal Miners - Prabhu, P; ., Umang; Jayakumar, Jyothi; Phanindra Kumar, Ch; ., . (International Journal of Engineering and Technology, 2018)
In this paper we are designing an intelligent wearable device for coal miners. This proposed system not only helps the workers in telling about the poisonous gases that are present but also tracks them if any mishap occurs. The device is provided with methane and carbon monoxide gas sensor. It ensures the supervision based on IoT (Internet of Things). We make use of mainly NRF module and RFID technology. RFID can easily track a person in case of an accident. Use of IoT helps us to make the database as well as helps us in communication to the nearest hospital if help needed.Â Â